2017
DOI: 10.5114/hpc.2017.70524
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Social and Environmental Predictors of Physical Activity in Mexican Adolescents

Abstract: Authors' contribution Wkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryBackground. Sedentarism and Physical Activity (PA) are considered main components of people's lifestyle and key indicators of health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
2
2
0
1
Order By: Relevance
“…Regarding the first aim, this research shows an alarming situation, since 100% of the girls and more than 70% of the boys declare themselves as physically inactive. Similar results are shown in other studies also carried out with Mexican adolescents in which girls had higher levels of physical inactivity than boys [ 37 , 50 , 51 ]. A possible explanation for these results could be that Mexican girls experience less satisfaction and fun in PE lessons than boys, so Mexican girls feel more boredom in the PE lessons [ 37 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the first aim, this research shows an alarming situation, since 100% of the girls and more than 70% of the boys declare themselves as physically inactive. Similar results are shown in other studies also carried out with Mexican adolescents in which girls had higher levels of physical inactivity than boys [ 37 , 50 , 51 ]. A possible explanation for these results could be that Mexican girls experience less satisfaction and fun in PE lessons than boys, so Mexican girls feel more boredom in the PE lessons [ 37 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the studies published by the WHO [36] indicate that Belarusian men were 1.5 times more active than women. Our own study also showed that male students undertook more physical activity (5118.0 MET-min/week) than female students (3433.5 MET-min/week), which confirms other studies conducted with the IPAQ [45][46][47].…”
Section: Discussionsupporting
confidence: 89%
“…In most of the selected international works the research group was formed by only youth attending secondary school [10,11,12,13,14,15,16], but some studies were also devoted to other populations. Cocca A. et al [17] researched people aged 9-24, starting from the third-grade pupils of primary school and ending with university graduates.…”
Section: Methods and Research Materialsmentioning
confidence: 99%